Preparation method of water-based coating for elastic finishing of filter material
Through the preparation method of silicone rubber latex with stable silicone rubber latex, the environmental pollution and instability problems of silicone rubber latex preparation of organic solvents and single emulsifiers are solved, and uniform finishing and efficient ash cleaning of the filter material surface is achieved, and the filter material is extended Service life.
Patent Information
- Application Number
- CN202411242045.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, the use of organic solvents to disperse high viscosity silicone rubber or a single emulsifier to prepare silicone rubber emulsions has problems such as environmental pollution, poor instability and uneven load, resulting in a decrease in breathable performance of the filter material and poor cleaning effect.
Using the preparation method of silicon sol-stable silicone rubber emulsion, the aqueous elastic coating is prepared by ultrasonic dispersion and high-speed shear homogeneous emulsification, combined with end-group functionalized polydimethylsiloxane and crosslinking agent, and uniformly coated on The surface of the filter material forms an elastic film to enhance the dust cleaning effect.
It improves the surface uniformity and dust cleaning performance of the filter material, extends the service life, reduces the operating resistance of dust removal equipment, reduces the dust cleaning frequency, and reduces environmental pollution.
Smart Images

Figure CN119121647A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional finishing of bag filter materials, and in particular to a method for preparing a water-based coating for elastic finishing of filter materials. Background Art
[0002] In the field of industrial production, with the development of technologies such as high-temperature resistant filter materials and pulse cleaning, bag filters have been increasingly widely used in the field of high-temperature and high-concentration flue gas treatment due to their excellent dust removal performance, and have gradually become one of the most efficient dust removal methods for industrial smoke filtration. However, single organic fiber materials such as high-temperature resistant filter materials such as polytetrafluoroethylene, polyphenylene sulfide, and aromatic polyimide often face problems such as limited performance, insufficient mechanical properties, and poor cleaning performance under special working conditions. They are often improved and solved through coating filter composite technology, that is, by preparing a multifunctional emulsion coating and compounding it to the surface of the filter material, so that the above high-temperature filter material has low resistance, easy cleaning, corrosion resistance and other multifunctional properties, so as to improve its wide application.
[0003] Previously, China Patent No. CN201310352417.X disclosed a preparation process for a high-precision double-layer base cloth needle-punched felt filter material, which uses fine denier fiber to make the surface layer, and has the advantages of small pore size, high porosity and filtration accuracy. However, its filter material uses a double-layer base cloth, and dust is easily adhered to its surface during the filtration process, and when pulse blowing is used for dust removal, the dust layer is not easy to fall off and clean; China Patent No. 202311642252.X discloses a preparation method for an easy-to-clean PTFE coated filter material, the surface of which is not easy to adhere to dust, and the dust layer is easy to blow off, which effectively reduces the operating resistance of the dust removal equipment and improves the dust removal efficiency of the filter material, but the coating on the surface of the filter material will also reduce its own air permeability and increase the rising rate of the surface resistance of the filter material during the filtration process, thereby resulting in a decrease in the filtering and cleaning performance of the filter material.
[0004] In the field of coated filter material composite technology, Chinese Patent No. 200910095421.6 discloses a method for preparing a fluororesin emulsion impregnating agent and a method for preparing a coated fabric cloth. After being impregnated with the prepared impregnating agent, the fabric cloth has the characteristics of no deformation, no shrinkage, no oil stain, and corrosion resistance under long-term heating. However, the raw material used in the prepared fluororesin emulsion impregnating agent is fluorine-containing resin, which is not environmentally friendly and can easily pollute the environment; Patent No. 202010077881.2 discloses a high-temperature resistant needle-punched filter felt with a PTFE coating, which is used to solve the problem that the filter felt coating is exposed for a long time, affecting the filtration effect and easily causing secondary pollution when the filter felt is cleaned. However, in actual use, the filter material resistance increases and the cleaning is not smooth due to uneven distribution of the emulsion and agglomeration of PTFE particles.
[0005] Among many elastic finishing materials, silicone rubber is widely used in elastic coatings and fabric elastic finishing. Silicone rubber elastomers are not only simple to prepare and low in cost, but also have good adhesion on the fiber surface, especially for hydrophobic fibers. They can enhance the resistance to mechanical effects such as tearing and abrasion during use. Its good resilience can effectively solve the problem that the dust layer of the filter material is difficult to fall off and clean. At present, most of the related patents on silicone rubber elastic finishing at home and abroad use highly toxic organic solvents to disperse high-viscosity silicone rubber, which is less environmentally friendly; or use a large amount of emulsifiers and a large amount of non-reactive surfactants to prepare silicone rubber emulsions, resulting in poor emulsion stability, short storage time, and low water resistance and mechanical strength of the film-forming material. Summary of the invention
[0006] In view of the problem that the existing use of organic solvents to disperse high-viscosity silicone rubber or the use of a single emulsifier to prepare silicone rubber emulsion is unstable, resulting in difficulty in combining with a filter material substrate and uneven loading, the present invention provides a method for preparing a silicone rubber emulsion stabilized by silica sol, which can effectively solve the environmental pollution caused by the use of organic solvents to prepare emulsions and the problems of instability and difficulty in storage when using a single emulsifier to prepare emulsions, improve the surface uniformity of the finished filter material, and avoid negative impact on the air permeability of the filter material.
[0007] The existing method of coating the dust-facing surface of the filter material to improve the cleaning effect of the filter material and solve the problem of incomplete dust layer shedding. Different from the prior art, the present invention provides a method for preparing an easy-to-clean water-based elastic coating based on the "elastic effect" mechanism of pulse cleaning imparted to the filter material surface. The filter material's air-purifying surface is the cleaning object. By arranging a layer of elastic coating on the air-purifying surface of the filter material, the elastic enhancement effect of the filter material itself is fully utilized, the maximum reverse acceleration during pulse jet cleaning is greatly increased, and the dust layer peeling effect on the dust-facing surface of the filter material is effectively improved, so that the filter material can be effectively regenerated, the cleaning frequency is greatly reduced, the speed of the filter material resistance increase is slowed down, the operating resistance of the dust removal equipment is effectively reduced, and the service life of the filter material is extended.
[0008] Another object of the present invention is to provide an aqueous coating composition for elastic finishing of filter materials prepared by the above method and a preparation method thereof.
[0009] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing a water-based coating for elastic finishing of filter materials, comprising the following steps:
[0010] (1) Preparation of silicone rubber emulsion A: dilute the silica sol to a certain concentration, then weigh a certain amount of emulsifier and add it to the silica sol of a certain concentration for ultrasonic dispersion, until it is left standing for at least 2 hours without creaming and stratification, thus obtaining a silica sol-emulsifier mixed dispersion with good compatibility; then add terminal functionalized polydimethylsiloxane to the above dispersion, adjust the pH of the emulsion to 4.5-9, and perform high-speed shear homogenization emulsification to obtain a stable silicone rubber emulsion A;
[0011] (2) Preparation of pre-crosslinked silicone rubber emulsion B: adding a certain amount of crosslinking agent to the above silicone rubber emulsion A, stirring at 200-400 r / min using a magnetic stirrer for at least 30 min, then adding a catalyst and a wetting agent and continuing to stir and mix uniformly to obtain pre-crosslinked silicone rubber emulsion B;
[0012] (3) Preparation of water-based elastic coating of filter media: The original filter media carrier is ultrasonically cleaned with anhydrous ethanol for 0.2 to 1.5 hours to remove fine particles and grease on the filter media surface and in the internal pores. Then, the pre-cross-linked silicone rubber emulsion B is coated on the clean air surface of the filter media for finishing. After being placed at room temperature for 20 to 40 minutes, it is placed in a vacuum drying oven at 80 to 150°C and dried for 1 to 3 hours. After the emulsion is completely cured, a layer of elastic film is formed on the surface of the filter media, thus obtaining the water-based elastic coating of the filter media.
[0013] Furthermore: the silica sol described in step (1) is any one of AS-30, AS-40, TM-50, PW-30, PW-50, HS-40 or a mixture of two or more in any ratio, the particle size of the silica sol used is 5 to 45 nm, the mass fraction of SiO2 in the silica sol is 20 to 50%, and the mass fraction of SiO2 in the diluted silica sol is 5 to 15%.
[0014] Furthermore, the emulsifier described in step (1) is any one of TX-10, OP-9, FA-10, AEC, sodium dodecylbenzene sulfonate, and hexadecyltrimethylammonium bromide, or a mixture of two or more of them in any ratio; and the mass concentration of the emulsifier in the silica sol-emulsifier mixed dispersion is 0.05-0.4%.
[0015] Furthermore: the ultrasonic power of the ultrasonic dispersion in step (1) is 30 to 120 W, and the ultrasonic time is 20 to 40 min.
[0016] Furthermore: the end-functionalized polydimethylsiloxane described in step (1) is any one of vinyl-terminated polydimethylsiloxane, hydroxyl-terminated polydimethylsiloxane, amino-terminated polydimethylsiloxane, hydrogen-containing silicone oil, or a mixture of two or more thereof in any ratio, and has a viscosity of 30 to 15000 cst.
[0017] Furthermore: the reagent used to adjust the pH of the emulsion in step (1) is any one of HCl, CH3COOH, NH3·H2O or a mixture of two or more in any ratio, and the molar concentration of the adjusted emulsion is 0.1-10 mol / L; the high-speed shear rate in step (1) is 5000-30000 rpm / min, and the processing time is 1-10 min.
[0018] Furthermore: the silicone rubber emulsion A described in step (1) is of oil-in-water type, and the droplet size of the emulsion is 0.5 to 50 μm.
[0019] Furthermore: the crosslinking agent described in step (2) is any one of trimethyltriethoxysilane, isobutyltrimethylsilane, and tetraethyl orthosilicate, or a mixture of two or more of them in any ratio, and the mass ratio of the crosslinking agent to the end-group functionalized polydimethylsiloxane is 0.01 to 0.3:1.
[0020] Further: the catalyst described in step (2) is any one of the organic tin compounds stannous octoate, dibutyltin dilaurate or titanate catalysts; the wetting agent is any one of Sivel 8378, JH-4020, TEGO 245, HT-198, HT-105, OT-75, PE-100, and its amount accounts for 0.001% to 0.07% of the water-based silicone rubber emulsion.
[0021] Further: the filter material described in step (3) is any one of PPS coated filter material, PTFE coated filter material, PET coated filter material, PPS, PTFE blended coated filter material, the finishing method of the pre-crosslinked silicone rubber emulsion B is any one of direct dipping method, electrostatic spraying method, spray gun spraying method and wire rod scraping method, and the finishing amount on the filter material is 10-120g / m 2 The curing temperature of the filter material after finishing described in step (3) is 25-160°C, and the curing time is 0.5-5h.
[0022] By adopting the above technical solution, the beneficial effects of the present invention are:
[0023] 1. The preparation process of the present invention is simple, green and safe. It uses linear polysiloxane as raw material, which ensures relatively excellent high temperature resistance, acid and alkali resistance and elasticity. The stability and dispersibility of the silicone elastomer emulsion can be regulated by adjusting the ratio of silica sol to emulsifier, the water-oil volume ratio and the pH of the emulsion.
[0024] 2. The present invention prepares silicone rubber emulsion and uses water as solvent to disperse uncrosslinked linear polysiloxane, which replaces the original method of using organic solvents as diluents to reduce the viscosity of silicone rubber, reduces harm to the environment and human body, and can also reduce production and application costs, making it easy to scale up production.
[0025] 3. The present invention prepares silicone rubber emulsion, adds curing agent for cross-linking, and when the water evaporates, these particles can irreversibly aggregate into silicone rubber elastomer. In addition, fillers, pigments and other additives are added as needed to prepare silicone rubber that meets different application requirements. Before the water evaporates to form a film, the system exists in the form of emulsion, and after the water evaporates, a silicone rubber film is formed.
[0026] 4. The present invention utilizes the advantages of water-based silicone elastomer emulsion, which is easy to use and has good adhesion to fibers compared to traditional silicone rubber, and elastically finishes the filter material by dipping, spraying, scraping, etc.; the water-based silicone elastomer emulsion can be evenly coated on the fiber surface, and can firmly adhere to and form layers of tightly bonded silicone elastomer films after water evaporates, and has excellent waterproof and anti-stick properties. In practical applications, lower pressure drop can be obtained, the cleaning time can be extended, and the service life of the filter material can be increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The appearance and optical microscope structure of the emulsion prepared using traditional surfactants are shown in the initial state after preparation and after the emulsion has been left to stand for 30 days;
[0028] Figure 2-1 is an optical microscope structure diagram of the oil-in-water silicone rubber emulsion prepared in Examples 1-4 of the present invention at different solid contents;
[0029] Figure 2-2 1 is a particle size diagram of the oil-in-water silicone rubber emulsion prepared in Examples 1-4 of the present invention during storage;
[0030] Figure 2-3 Graph showing the static stability of the oil-in-water silicone rubber emulsions prepared in Examples 1-4 of the present invention;
[0031] Figure 2-4 1 is a pH stability diagram of the oil-in-water silicone rubber emulsion prepared in Examples 1-4 of the present invention;
[0032] Figure 2-5 Graph showing the centrifugal stability of the oil-in-water silicone rubber emulsions prepared in Examples 1-4 of the present invention;
[0033] Figure 3 Graphs showing water contact angles of different SiO2 and silicone oil-in-water silicone rubber emulsions prepared in Examples 1-4 of the present invention;
[0034] Figure 4 Scanning electron micrographs of the water-based elastic coating finishing filter material prepared in Examples 1-4 (Figure b), the water-based elastic coating finishing filter material prepared in the comparative example (c), and the original filter material (Figure a);
[0035] Figure 5-1 to Figure 5-4 A comparison chart of the dust removal rates of the water-based elastic coating filter materials prepared in Examples 1-4 with different finishing amounts and the dust removal rates of the original filter materials;
[0036] Figure 6 A comparison chart of the maximum reverse acceleration of the water-based elastic coating filter material prepared in Examples 1-4 at different finishing amounts and the maximum reverse acceleration of the original filter material;
[0037] Figure 7 The instantaneous change curve of the acceleration of the PPS filter material prepared in Example 1 under different amounts of water-based elastic coating during spraying and the acceleration curve of the original filter material are shown. DETAILED DESCRIPTION
[0038] The embodiments of the present invention are described in detail below. The examples of the embodiments are intended to explain the present invention and should not be construed as limiting the present invention. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.
[0039] 1. Preparation method of water-based elastic coating
[0040] Example 1
[0041] 7.0g AS-40 was added to 40ml deionized water and ultrasonically dispersed at 30W ultrasonic power for 10s, then 0.4g emulsifier OP-9 was added, and a magnetic stirrer was used to stir at 400r / min for 0.5h to obtain a AS-40-OP-9 dispersion with good compatibility. 40g hydroxyl-terminated polydimethylsiloxane with a viscosity of 5000cst was added to the above AS-40-OP-9 dispersion, and homogenized shear emulsification was performed at 8000rpm / min for 6min, and then 20 drops of 1mol / L HCl and 0.1mol / L NH3·H2O were added to adjust the pH value of the emulsion, and shear emulsification was performed again. The pH adjustment and shear emulsification process were repeated until the pH of the emulsion was 8.12, and a stable silicone rubber emulsion A containing AS-40-OP-9 was obtained.
[0042] Weigh 20 g of the above-mentioned stable silicone rubber emulsion A, add 1.5 g of methyltrimethoxysilane, use a magnetic stirrer to stir at 200 r / min for 30 min, add 0.04 g of dibutyltin dilaurate and 0.06 g of wetting agent Si vel 800 after the emulsion is completely cross-linked, and continue to stir and mix evenly to obtain pre-cross-linked silicone rubber emulsion B for use.
[0043] The original coated filter material was cut into a diameter of about 15 cm, and ultrasonically cleaned with anhydrous ethanol for 20 minutes to remove fine particles and grease on the surface and internal pores of the filter material, and then placed in a 100°C oven for 2 hours, and then placed in a vacuum drying oven at 120°C to remove moisture inside the filter material, and the weight was recorded. The above-mentioned pre-crosslinked silicone rubber emulsion B was sprayed on the surface of the filter material using a spray gun spray method. After being placed at room temperature for half an hour, the surface of the filter material was flattened, and then dried in a vacuum drying oven at 150°C to prepare an elastic coating filter material prepared by spraying.
[0044] Example 2
[0045] 12.0g TW-50 was added to 70ml deionized water and ultrasonically dispersed at 30W ultrasonic power for 10s, then 0.5g emulsifier OP-9 was added, and a magnetic stirrer was used to stir at 400r / min for 2h to obtain a TW-50-OP-9 dispersion with good compatibility. 40g hydroxyl-terminated polydimethylsiloxane with a viscosity of 1000cst was added to the above TW-50-OP-9 dispersion, and homogenized shear emulsification was performed at 12000rpm / min for 10min, and then 1ml 1mol / L HCl and 0.1mol / L NH3·H2O were added to adjust the pH value of the emulsion, and shear emulsification was performed again. The pH adjustment and shear emulsification process were repeated until the pH of the emulsion was 7.53, and a stable silicone rubber emulsion A containing TW-50-OP-9 was obtained.
[0046] Weigh 30 g of the above-mentioned stable silicone rubber emulsion A, add 2.0 g of tetraethyl orthosilicate, use a magnetic stirrer to stir at 250 r / min for 20 min, add 0.06 g of dibutyltin dilaurate and 0.1 g of wetting agent S ive l 800 after the emulsion is completely cross-linked, and continue to stir and mix evenly to obtain pre-cross-linked silicone rubber emulsion B for use.
[0047] The original coated filter material was cut into a diameter of about 15 cm, and ultrasonically cleaned with anhydrous ethanol for 20 minutes to remove fine particles and grease on the surface and internal pores of the filter material, and then placed in a 100°C oven for 2 hours, and then placed in a vacuum drying oven at 120°C to remove moisture inside the filter material, and the weight was recorded. The above-mentioned pre-crosslinked silicone rubber emulsion B was sprayed on the surface of the filter material using a spray gun spray method. After being placed at room temperature for half an hour, the surface of the filter material was flattened, and then dried in a vacuum drying oven at 150°C to prepare an elastic coating filter material prepared by spraying.
[0048] Example 3
[0049] Take 20.0g TW-50 and add it to 80ml deionized water, and ultrasonically disperse it for 30s at 30W ultrasonic power. Then add 0.3g emulsifier sodium dodecylbenzene sulfonate SDBS in turn, and stir it at 400r / min for 4h using a magnetic stirrer to obtain a TW-50-SDBS dispersion with good compatibility. Add 100g hydroxyl-terminated polydimethylsiloxane with a viscosity of 5000cst to the above TW-50-SDBS dispersion, and homogenize and shear emulsify it at 19000rpm / min for 8min, then add 2ml 1mol / L HCl and 0.1mol / L NH3·H2O to adjust the pH value of the emulsion, and shear emulsify it again. Repeat the pH adjustment and shear emulsification process until the pH of the emulsion is 6.22, and obtain a silicone rubber emulsion A containing TW-50-SDBS.
[0050] Weigh 30 g of the above-mentioned stable silicone rubber emulsion, add 2.5 g of methyltrimethoxysilane, use a magnetic stirrer to stir for 30 min at 200 r / min, add 0.1 g of stannous octoate and 0.2 g of wetting agent TEGO 245 after the emulsion is completely cross-linked, and continue to stir and mix evenly to obtain pre-cross-linked silicone rubber emulsion B for use.
[0051] The original coated filter material was cut into a diameter of about 15 cm, and ultrasonically cleaned with anhydrous ethanol for 20 minutes to remove fine particles and grease on the surface and internal pores of the filter material, and then placed in a 100°C oven for 2 hours, and then placed in a vacuum drying oven at 120°C to remove moisture inside the filter material, and the weight was recorded. The above-mentioned pre-crosslinked silicone rubber emulsion B was sprayed on the surface of the filter material using a spray gun spray method. After being placed at room temperature for half an hour, the surface of the filter material was flattened, and then dried in a vacuum drying oven at 150°C to prepare an elastic coating filter material prepared by spraying.
[0052] Example 4
[0053] 15.0g HS-40 was added to 75ml deionized water and ultrasonically dispersed for 30s at 30W ultrasonic power, and then 0.4g emulsifier FA-10 was added in turn and stirred at 400r / min for 4h using a magnetic stirrer to obtain a HS-40-FA-10 dispersion with good compatibility. 100g hydroxyl-terminated polydimethylsiloxane with a viscosity of 10000cst was added to the above HS-40-FA-10 dispersion, and homogenized shear emulsification was performed at 13000rpm / min for 15min, and then 2ml 1mol / L HCl and 0.1mol / L NH3·H2O were added to adjust the pH value of the emulsion, and shear emulsification was performed again. The pH adjustment and shear emulsification process were repeated until the pH of the emulsion was 4.84, and a stable silicone rubber emulsion A containing composite HS-40-FA-10 particles was obtained.
[0054] Weigh 40 g of the above-mentioned stable silicone rubber emulsion A, add 4.5 g of isobutyl triethoxysilane, use a magnetic stirrer to stir at 350 r / min for 25 min, add 0.08 g of titanate catalyst and 0.08 g of wetting agent TEGO245 after the emulsion is completely cross-linked, continue to stir and mix evenly, and obtain pre-cross-linked silicone rubber emulsion B for use.
[0055] The original coated filter material was cut into a diameter of about 15 cm, and ultrasonically cleaned with anhydrous ethanol for 20 minutes to remove fine particles and grease on the surface and internal pores of the filter material, and then placed in a 100°C oven for 2 hours, and then placed in a vacuum drying oven at 120°C to remove moisture inside the filter material, and the weight was recorded. The above-mentioned pre-crosslinked silicone rubber emulsion B was sprayed on the surface of the filter material using a spray gun spray method. After being placed at room temperature for half an hour, the surface of the filter material was flattened, and then dried in a vacuum drying oven at 150°C to prepare an elastic coating filter material prepared by spraying.
[0056] Comparative Example 1
[0057] 4.0 g of emulsifier TX-10 was added to 40 ml of deionized water and ultrasonically dispersed for 30 seconds at 30 W ultrasonic power to obtain an emulsifier dispersion with good dispersibility, and then added to 80 g of hydroxyl-terminated polydimethylsiloxane with a viscosity of 5000 cst, and homogenized and sheared emulsified for 8 minutes at 19000 rpm / min, and then 3 ml of 1 mol / L HCl and 1 mol / L NH3·H2O were added to adjust the pH value of the emulsion, and sheared emulsification was performed again, and the pH adjustment and sheared emulsification processes were repeated until the pH value of the emulsion was 8.94, thus obtaining TX-10 stabilized silicone rubber emulsion A. The cross-linking and curing of silicone rubber emulsion A and the preparation process of elastic coating filter material are the same as those in Examples 1-4.
[0058] Figure 1 The following are the appearance and droplet micrographs of the silicone rubber emulsion prepared by the conventional surfactant method corresponding to the comparative example in its initial state after preparation and after the emulsion was left to stand for 30 days. It can be seen that compared with the silicone rubber emulsion prepared by the surfactant method, the silicone rubber emulsion stabilized by silica sol and a trace amount of emulsifier ( Figure 2-3 ) After standing for 30 days, the macroscopic dispersion state was similar to the initial state, and the overall stability of the emulsion was good. The emulsion was centrifuged at 3000r / min for 30min without obvious stratification ( Figure 2-5 ), indicating that long-term storage of the emulsion will not destroy the stability of the silicone rubber emulsion itself; Figure 2-2 For the corresponding Figure 2-1The particle size distribution curve with a solid content of about 33% shows that the emulsion particle size is mostly distributed between 1 and 10 μm, and the overall particle size distribution of the emulsion is relatively concentrated, with a small particle size. The silicone rubber emulsion prepared by the surfactant method shows a large difference in macroscopic dispersion state from the initial state after standing for 30 days. The emulsion shows obvious stratification and the emulsion droplet size increases significantly, indicating that the emulsion in the control group has poor stability and is not suitable for long-term storage.
[0059] Figure 4 The scanning electron microscope images of the elastic coating filter material prepared in Examples 1-4 and the comparative example and the original filter material. It can be seen that compared with the elastic coating filter material prepared by the surfactant method (Figure c), the microscopic morphology of Example 1-4 sprayed on the filter material surface (Figure b) is more uniform, forming a layer of elastic film with larger pores on the filter material surface, while Figure c clearly shows that the emulsion is not evenly coated on the filter material surface, and the pores on the filter material surface are seriously blocked. Figure 1 From the microscopic image of the emulsion droplets, it can be clearly seen that the overall particle size of the silicone rubber emulsion prepared in the comparative example is relatively large, which can easily cause uneven coating. The silicone rubber particles prepared in Examples 1-4 are relatively small and distributed more concentratedly, so they are more evenly coated on the filter material surface and will not cause pore clogging.
[0060] 2. Performance test of water-based elastic coating composition
[0061] 1. Cleaning performance test
[0062] In order to investigate the dust cleaning performance of the obtained silicone rubber emulsion loaded filter material, VDI filtration-dust cleaning experiments were carried out using the elastic coating filter materials prepared in Examples 1-4. The specific experimental process is as follows:
[0063] The above filter material with elastic coating was tested for dust cleaning performance through a dust filtration efficiency test system to evaluate the cleaning performance of the prepared silicone rubber emulsion loaded filter material, which was used as the experimental group. The cleaning performance of the elastic coating filter material is represented by the dust stripping rate K, and the calculation formula is as follows:
[0064]
[0065] Where: P is the resistance set when triggering dust cleaning, 1000Pa; P last is the resistance Pa of the filter material after the test; P0 is the resistance Pa of the filter material before the test;
[0066] Table 1 Comparison of dust removal rate of PPS coated filter material before and after silicone rubber emulsion finishing
[0067]
[0068] Table 1 shows the comparison of dust stripping rate data of the silicone rubber emulsion containing composite particles prepared in Examples 1-3 loaded onto the clean air surface of the PPS coated filter material under basically the same air permeability conditions. It can be found that compared with the original filter material, Examples 1-3 have a dust stripping rate of 30 g / m 2 Around, the changes in its air permeability are very small. When conducting the filtration-cleaning experiment, the dust stripping rate of the filter material in the initial stage, aging stage, and stable aging stage increased significantly. Example 1 has improved cleaning performance by 10%, 57%, and 33% at 30C1, 10000agi ng, and 30C2, respectively; Example 2 has improved cleaning performance by 12%, 60%, and 30% at 30C1, 10000agi ng, and 30C2, respectively; Example 3 has improved cleaning performance by 6%, 58%, and 28% at 30C1, 10000agi ng, and 30C2, respectively; combined Figure 7 The stable silicone rubber emulsion is evenly loaded on the clean air surface of the filter material, forming a layer of elastic film with larger pores on the surface of the filter material, which is more conducive to dust cleaning during pulse spraying and will not cause obvious influence on the air permeability and filtration performance of the filter material itself.
[0069] Table 2 Comparison of dust removal rate of PPS coated filter material silicone rubber emulsion before and after different finishing
[0070]
[0071]
[0072] Table 2 is a comparison of the dust removal rate of the silicone rubber emulsion containing composite particles prepared in Example 4 loaded on the clean air surface of the PPS coated filter material at different finishing amounts. It can be seen from the table that in the range of finishing amounts of 10 to 50, with the increase of the finishing amount, it shows a trend of first increasing and then decreasing, and in Example 5, the finishing amount is 22.48 g / m 2 The cleaning performance is the best, and the cleaning performance of the three stages of 30C1, 10000agi ng, and 30C2 are respectively improved by 11%, 50%, and 30% compared with the original filter material of Comparative Example 2; compared with Comparative Example 4 (silicone rubber emulsion prepared with traditional emulsifier) at the same finishing amount, the cleaning performance of the three stages of 30C1, 10000agi ng, and 30C2 is significantly reduced. The possible reason is that the elastic coating will cause the air permeability of the filter material to decrease after the surface of the filter material is finished. However, with the increase in the finishing amount, the elastic coating will offset the increase in pressure drop caused by the decrease in air permeability, while playing the role of the coating's own elasticity, increasing the maximum reverse acceleration of the filter material during pulse blowing, thereby reducing the residual pressure drop during cleaning and improving the cleaning performance. However, when the finishing amount of the filter material is high, when the finishing amount of Comparative Example 3 is increased to 120g / m 2When the air permeability drops significantly, the dust removal rate during the filtration and cleaning process is significantly reduced, which affects the cleaning performance of the filter material. The cleaning performance of the three stages of 30C1, 10000agi ng, and 30C2 is 10%, 16%, and 25% lower than that of the original filter material in Comparative Example 2. Therefore, it is necessary to balance the synergistic relationship between air permeability and finishing amount and seek the optimal finishing amount process conditions.
[0073] Table 3 Comparison of dust removal rates of different coated filter materials before and after silicone rubber emulsion finishing
[0074]
[0075]
[0076] Table 3 is a comparison of dust removal rates of the silicone rubber emulsion containing composite particles prepared in Example 4 loaded onto different coated filter materials. Combining Table 1 and Table 2, it can be seen that the four filter materials have a cleaning amount of 20-30 g / m 2 The optimal finishing amount for the best cleaning performance in the range is slightly different, but the finishing of the elastic coating has a positive effect on the cleaning of the filter media. Among them, the cleaning performance improvement of the PTFE coated filter media after finishing is the worst. The possible reason is that the PTFE coated original filter media is relatively soft and thin, and it is easy to block the holes when loading and finishing, resulting in the worst improvement in its cleaning performance; the PPS coated filter media has a finishing amount of 22.48g / m 2 The cleaning performance was the best, and the cleaning performance of 30C1, 10000agi ng, and 30C2 stages increased by 11%, 50%, and 30% respectively; the PET coated filter material was 30.56g / m 2 The cleaning performance of the original PET coated filter material in comparative example 6 was improved by 14%, 53% and 20% respectively at 30C1, 10000agi ng and 30C2. The cleaning performance of the PPS and PTFE blended coated filter material was improved by 35.34g / m 2 The cleaning performance is improved by 13%, 50% and 28% respectively in the three stages of 30C1, 10000agi ng and 30C2 compared with the original PPS and PTFE membrane filter materials in comparative example 7.
[0077] 2. Maximum reverse acceleration performance test
[0078] In order to examine the elastic properties of the filter material after being loaded and processed by the silicone rubber emulsion, the elastic coating filter material prepared in Examples 1-4 was used to test the maximum reverse acceleration and the maximum forward acceleration of Examples 1-9 and Comparative Examples 1-7. The specific data are as follows:
[0079] Table 1 shows the maximum reverse acceleration data of the prepared silicone rubber emulsion containing composite particles (experimental group) prepared in Examples 1-4 loaded onto the clean air surface of the original membrane filter material, and the comparison of the finished filter material with different finishing amounts and the original filter material with the same air permeability. It can be found that compared with the original filter material, the four organic synthetic fiber filter materials have a finishing amount of 10-120g / m 2 When the filter material within the range undergoes maximum deformation, the acceleration will increase, and with the increase of the finishing amount, it shows a trend of first increasing and then decreasing, which is consistent with the changing trend of the dust stripping rate under different finishing amounts in Table 1, Table 2, and Table 3. This also verifies that the load finishing of the elastic coating increases the frequency of filter material vibration during pulse jet cleaning, thereby showing a larger value of reverse acceleration, which is more conducive to cleaning.
[0080] Table 2 Comparison of maximum reverse acceleration before and after silicone rubber emulsion finishing
[0081]
[0082] Although the present invention has been specifically shown and described in conjunction with the preferred embodiments, it should be understood by those skilled in the art that various changes may be made to the present invention in form and details without departing from the spirit and scope of the present invention as defined by the appended claims, all of which are within the scope of protection of the present invention.
Claims
1. A method for preparing a water-based coating for elastic finishing of filter materials, characterized in that: The following steps are involved: (1) Preparation of silicone rubber emulsion A: dilute the silica sol to a certain concentration, then weigh a certain amount of emulsifier and add it to the silica sol of a certain concentration for ultrasonic dispersion, until it is left standing for at least 2 hours without creaming and stratification, thus obtaining a silica sol-emulsifier mixed dispersion with good compatibility; then add terminal functionalized polydimethylsiloxane to the above dispersion, adjust the pH of the emulsion to 4.5-9, and perform high-speed shear homogenization emulsification to obtain a stable silicone rubber emulsion A; (2) Preparation of pre-crosslinked silicone rubber emulsion B: adding a certain amount of crosslinking agent to the above silicone rubber emulsion A, stirring at 200-400 r / min using a magnetic stirrer for at least 30 min, then adding a catalyst and a wetting agent and continuing to stir and mix uniformly to obtain pre-crosslinked silicone rubber emulsion B; (3) Preparation of water-based elastic coating of filter media: The original filter media carrier is ultrasonically cleaned with anhydrous ethanol for 0.2 to 1.5 hours to remove fine particles and grease on the filter media surface and in the internal pores. Then, the pre-cross-linked silicone rubber emulsion B is coated on the clean air surface of the filter media for finishing. After being placed at room temperature for 20 to 40 minutes, it is placed in a vacuum drying oven at 80 to 150°C and dried for 1 to 3 hours. After the emulsion is completely cured, a layer of elastic film is formed on the surface of the filter media, thus obtaining the water-based elastic coating of the filter media.
2. The method for preparing a water-based coating for elastic finishing of filter materials according to claim 1, characterized in that: The silica sol described in step (1) is any one of AS-30, AS-40, TM-50, PW-30, PW-50, HS-40 or a mixture of two or more thereof in any ratio, the particle size of the silica sol used is 5 to 45 nm, the mass fraction of SiO2 in the silica sol is 20 to 50%, and the mass fraction of SiO2 in the diluted silica sol is 5 to 15%.
3. The method for preparing a water-based coating for elastic finishing of filter materials according to claim 1, characterized in that: The emulsifier described in step (1) is any one of TX-10, OP-9, FA-10, AEC, sodium dodecylbenzene sulfonate, and hexadecyltrimethylammonium bromide, or a mixture of two or more of them in any ratio; the mass concentration of the emulsifier in the silica sol-emulsifier mixed dispersion is 0.05-0.4%.
4. The method for preparing a water-based coating for elastic finishing of filter materials according to claim 1, characterized in that: The ultrasonic power of the ultrasonic dispersion in step (1) is 30 to 120 W, and the ultrasonic time is 20 to 40 minutes.
5. The method for preparing a water-based coating for elastic finishing of filter materials according to claim 1, characterized in that: The end-functionalized polydimethylsiloxane described in step (1) is any one of vinyl-terminated polydimethylsiloxane, hydroxyl-terminated polydimethylsiloxane, amino-terminated polydimethylsiloxane, and hydrogen-containing silicone oil, or a mixture of two or more of them in any ratio, and has a viscosity of 30 to 15000 cst.
6. The method for preparing a water-based coating for elastic finishing of filter materials according to claim 1, characterized in that: The reagent used for adjusting the pH of the emulsion in step (1) is any one of HCl, CH3COOH, NH3·H2O or a mixture of two or more of them in any ratio, and the molar concentration of the adjusted emulsion is 0.1-10 mol / L; the high-speed shear rate in step (1) is 5000-30000 rpm / min, and the processing time is 1-10 min.
7. The method for preparing a water-based coating for elastic finishing of filter materials according to claim 1, characterized in that: The silicone rubber emulsion A described in step (1) is of oil-in-water type, and the droplet size of the emulsion is 0.5 to 50 μm.
8. The method for preparing a water-based coating for elastic finishing of filter materials according to claim 1, characterized in that: The crosslinking agent described in step (2) is any one of trimethyltriethoxysilane, isobutyltrimethylsilane, and ethyl orthosilicate, or a mixture of two or more of them in any ratio, and the mass ratio of the amount thereof to the end-group functionalized polydimethylsiloxane is 0.01 to 0.3:
1.
9. The method for preparing a water-based coating for elastic finishing of filter materials according to claim 1, characterized in that: The catalyst described in step (2) is any one of the organic tin compounds stannous octoate, dibutyltin dilaurate or titanate catalysts; the wetting agent is any one of Sivel 8378, JH-4020, TEGO 245, HT-198, HT-105, OT-75, PE-100, and its usage accounts for 0.001% to 0.07% of the water-based silicone rubber emulsion.
10. The method for preparing a water-based coating for elastic finishing of filter materials according to claim 1, characterized in that: The filter material described in step (3) is any one of PPS coated filter material, PTFE coated filter material, PET coated filter material, PPS, PTFE blended coated filter material, and the finishing method of the pre-crosslinked silicone rubber emulsion B is any one of direct dipping method, electrostatic spraying method, spray gun spraying method and wire rod scraping method, and the finishing amount on the filter material is 10-120g / m 2 The curing temperature of the filter material after finishing described in step (3) is 25-160°C, and the curing time is 0.5-5h.
Citation Information
Patent Citations
Preparation of fluoro-resin emulsion dipping agent and preparation of coated fabric
CN101463562A
High-precision double-layer base fabric needled felt filter material and preparation process thereof
CN103432826A
High-temperature-resistant needled filter felt with PTFE coating layer
CN111111339A
Preparation method of PTFE (Polytetrafluoroethylene) membrane filter material capable of easily cleaning dust
CN117643764A
Polydimethylsiloxane / polyetherimide (PDMS / PEI) fixed carrier composite film containing amino group and preparation method and application thereof
CN102500242A
